2013
DOI: 10.1016/j.jsps.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel loaded carrier based biodegradable polymeric implants: Preparation and in vitro characterization

Abstract: The objective of this study was to develop paclitaxel (PTX) loaded poly(ε-caprolactone) (PCL) based tiny implants. β-Cyclodextrin (β-CD) and polyethylene glycol (PEG 6000) were used to enhance solubility and release of the drug in the phosphate buffer saline pH 7.4. Implants were evaluated in terms of color, shape, thickness, surface area, weight, drug content. Developed implants were characterized for their surface morphology (SEM analysis), drug physical state by thermal analysis (DSC studies), crystalline n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 13 publications
5
14
0
Order By: Relevance
“…For instance, peak shifts were recorded in all encapsulations (catalase‐γCD complex encapsulation into PCL nanofiber, catalaze‐γCD physical mixture encapsulation into PCL nanofibers and catalase encapsulation into PCL nanofibers) at pure PCL peak values of 3444, 2948, 1294, and 1240 cm −1 in the FT‐IR spectrum. The adsorption band at 3444 cm −1 corresponds to OH vibrations, 2948 cm −1 corresponds to CH stretching, 1294 cm −1 corresponds to CO and CC stretching and the peak at 1240 cm −1 corresponds to antisymmetrical COC stretching vibrations …”
Section: Resultsmentioning
confidence: 99%
“…For instance, peak shifts were recorded in all encapsulations (catalase‐γCD complex encapsulation into PCL nanofiber, catalaze‐γCD physical mixture encapsulation into PCL nanofibers and catalase encapsulation into PCL nanofibers) at pure PCL peak values of 3444, 2948, 1294, and 1240 cm −1 in the FT‐IR spectrum. The adsorption band at 3444 cm −1 corresponds to OH vibrations, 2948 cm −1 corresponds to CH stretching, 1294 cm −1 corresponds to CO and CC stretching and the peak at 1240 cm −1 corresponds to antisymmetrical COC stretching vibrations …”
Section: Resultsmentioning
confidence: 99%
“…The characteristic peaks of PCL nanofibers were observed at 1730 cm −1 , 732 cm −1 , 840-1470 cm − 1 , 2892 cm − 1 , and 2930 cm − 1 . PTX loaded PCL-PF showed peaks at 2948 cm −1 and 1729 cm − 1 for C\H sp3 and C_O stretch, respectively; drug peaks were disappeared in composite fibers, may be due to drug was completely entrapped in the polymer fibers or polymeric amorphous surface since their concentration is also much less [29]. Results of FT-IR studies revealed no evidence of chemical interaction of drug with polymers.…”
Section: Morphology By Fe-semmentioning
confidence: 92%
“…1, the structure of PTX offers a variety of functional groups to form bonds with P123. FTIR spectra of the samples loaded with PTX showed additional peaks of PTX molecule at 1,072, 1,248, 1,370, and 2,965 12 cm −1 that were assigned to C-O stretch, C-N stretch, CH 3 bending, and =C-H structure, respectively [33,34]. However, resonance intensities and morphologies varied between samples.…”
Section: Investigation Of Ptx and Pluronic Interaction Using Ftir Andmentioning
confidence: 99%